ANALISIS PENGARUH INFORMASI AKUNTANSI DAN NON AKUNTANSI TERHADAP UNDERPRICING (STUDI PADA PERUSAHAAN SEKTOR JASA, PERDAGANGAN: DAN INVESTASI YANG MELAKUKAN IPO DI BURSA EFEK INDONESIA TAHUN 2008 – 2016 - Lestari, Novita; Rasyid, Elly; Lumbantoruan, Rutman (Universitas Kristen Indonesia, 2017)
The objective of this research is to examine the effect of company’s age, company’s size, Debt to Equity Ratio (DER), Return on Assets (ROA) and Earning Per Share (EPS). Testing hypotheses are conducted using multiple regression models with observation from 35 sample IPO in service trade and investment companies that listed in Indonesia Stock Exchange during the period of 2008-2016. The empirical result show that company’s age and DER have negative significant effect on underpricing level. However company’s size, ROa and EPS have no significant effect on underpricing level.Keywords : IPO, Underpricing, company’s age, company’s size, Debt to Equity Ratio (DER), Return on Assets (ROA), and Earning Per Share (EPS).